Symptomatic Very Delayed Parent Artery Occlusion After Flow Diversion Stent Embolization - ARAI, Hajime; NONAKA, Senshu; YAMAMOTO, Munetaka; TERANISHI, Kosuke; OISHI, Hidenori (Neurologia medico-chirurgica, 2016)
Flow diversion stents (FDSs) are constructed from high-density braided mesh, which alters intra-aneurysmal hemodynamics and leads to aneurysm occlusion by inducing thrombus formation. Although there are potential complications associated with FDS embolization, one of the serious complications is the parent artery occlusion due to the in-stent thrombosis. A 72-year-old woman with a symptomatic giant fusiform aneurysm in the cavernous segment of ICA underwent single-layer pipeline embolization device (PED) embolization. Six-month and 1-year follow-up conventional angiographies showed the residual blood flow in the aneurysm. Two-year follow-up MRI showed the aneurysm sac shrinkage and the antiplatelet therapy was discontinued. The patient suffered from symptomatic parent artery occlusion due to the in-stent thrombosis, 4 months after antiplatelet therapy discontinuation. The patient with the incompletely occluded aneurysm after PED embolization should be given long-term antiplatelet therapy because of the risk of delayed parent artery occlusion.